Allelopathic effect of Oocystis borgei culture on Microcystis aeruginosa. Issue 11 (12th May 2022) - Wang, Xiaoqian; Zhang, Yulei; Li, Changling; Huang, Xianghu; Li, Feng; Wang, Xinyu; Li, Guanbao
ABSTRACT: This study evaluated the possibility of using Oocystis borgei to prevent and control harmful algae blooms. Firstly, Microcystis aeruginosa and O. borgei were co-cultured to assess the competition for nutrients between them. Different physiological and biochemical parameters, such as growth, cell membrane permeability and esterase activities were determined in exudate culture experiment to investigate allelopathic effects of O. borgei culture and mixed cultures ( O. borgei and M. aeruginosa ) at different growth phase on harmful microalgae ( M. aeruginosa ). Results showed that O. borgei could significantly inhibited M. aeruginosa when volume ratios were 4:1 and 1:1 ( M. aeruginosa: O. borgei ) in co-culture experiment. Further, it was found that the membrane system of M. aeruginosa was disintegrated by the culture filtrate of O. borgei at exponential phase. In addition, esterase activities and photorespiration were significantly inhibited. In conclusion, O. borgei exhibited different allelopathic effects at different growth phase. Its exponential phase showed a significant inhibitory effect, while no inhibitory effect was observed at the decline phase. GRAPHICAL ABSTRACT: UF0001